Morchella esculenta mushroom polysaccharide attenuates diabetes and modulates intestinal permeability and gut microbiota in a type 2 diabetic mice model - Rehman, Ata Ur; Siddiqui, Nimra Zafar; Farooqui, Nabeel Ahmed; Alam, Gulzar; Gul, Aneesa; Ahmad, Bashir; Asim, Muhammad; Khan, Asif Iqbal; Xin, Yi; Zexu, Wang; Song Ju, Hyo; Xin, Wang; et al. (Frontiers in Nutrition, 2022)
Type 2 diabetes mellitus (T2DM) is a health issue that causes serious worldwide economic problems. It has previously been reported that natural polysaccharides have been studied with regard to regulating the gut microbiota, which plays an important role in T2DM. Here, we investigate the effects of Morchella esculenta polysaccharide (MEP) on a high-fat diet (HFD) and streptozotocin (STZ)-induced T2DM in BALB/c mice. The administration of MEP effectively regulated hyperglycemia and hyperlipidemia and improved insulin sensitivity. We also determined an improvement in gut microbiota composition by 16sRNA pyrosequencing. Treatment with MEP showed an increase in beneficial bacteria, i.e., Lactobacillus and Firmicutes, while the proportion of the opportunistic bacteria Actinobacteria, Corynebacterium, and Facklamia decreased. Furthermore, the treatment of T2DM mice with MEP resulted in reduced endotoxemia and insulin resistance-related pro-inflammatory cytokines interleukin 1β (IL-1β), tumor necrosis factor-alpha (TNF-α), and interleukin 6 (IL-6). Moreover, MEP treatment improved intestinal permeability by modulating the expression of the colon tight-junction proteins zonula occludens-1 (ZO-1), occludin, claudin-1, and mucin-2 protein (MUC2). Additionally, MEP administration affects the metagenome of microbial communities in T2DM mice by altering the functional metabolic pathways. All these findings suggested that MEP is a beneficial prebiotic associated with ameliorating the gut microbiota and its metabolites in T2DM.